Predicting Insect Pest Outbreaks Using Climate Models and Remote Sensing - Chaturvedi, Gaurav; Naveen, Gudipati; Jan, Ulfat; V S, Adarsh; Mishra, Ambika Prasad; Mishra, Suchismita; Khokhar, Chetna; K, Thiruvengadam (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Insect pest outbreaks threaten agricultural productivity and global food security. Predicting their outbreaks is crucial for implementing effective pest management strategies. Traditional pest control measures often rely on reactive interventions, leading to significant economic losses. However, climate models and remote sensing technologies have emerged as powerful tools for predicting pest outbreaks before they occur. Climate models analyze atmospheric conditions to forecast pest behaviour, while remote sensing provides real-time data on environmental factors influencing pest populations. This paper discusses the integration of these technologies, highlighting key methodologies, case studies, challenges, and future directions in pest outbreak prediction. The findings underscore the importance of interdisciplinary approaches in developing early warning systems and sustainable pest management strategies.